Blinky Bill and the rabbit's birthday party - Odell, Carol (Sydney : Angus and Robertson, 1971)
Blinky Bill greatly enjoys himself at a rabbit's birthday party but when he pulls Madam Hare's tail a fight breaks out and he is forced to leave.
Keywords: Koala -- Juvenile fiction. Birthdays -- Juvenile fiction. Behavior -- Juvenile fiction